Analisis Prudential Principle pada Pembiayaan Murabahah Produk KPR Indent BTN IB di Bank Tabungan Negara Syariah Cabang Malang - Ridha Clasnita Thulusia; Khusnudin Khusnudin (Journal of Finance and Islamic Banking, 2019)
The prudential principle is a guideline in bank management that must be adhered to create healthy, strong and efficient banking by statutory provisions. One of the business activities that must be carried out prudently is fund distribution. Prudential Principle is said to be important because it relates to the interests of customers who entrust their customers, as written in Law Article 36 Number 21 concerning Sharia Banking. During the research period, BTN KCS Malang was able to increase the realization of BTN iB Indent KPR financing. It was interesting for researchers to find out about the application of the Prudential Principle to Murabaha financing products. This study uses a descriptive qualitative approach that aims to determine the Prudential Principle conducted by BTN KCS Malang in distributing Murabaha financing. The research respondents consisted of internal parties of banks and KPR Indent BTN iB financing customers. The results showed that Malang KCS BTN used 5C analysis in analyzing prospective Murabaha financing customers. Prudential Principle has been done properly and carefully in the distribution of murabaha financing.